Study on the sensitivity enhancement of fiber SPR sensor by gold nanorods. Issue 4 (3rd August 2021) - Wang, Rui; Liu, Chunlan; Wei, Yong; Su, Yudong
Abstract : Purpose: This paper aims to study the sensitivity enhancement effect of the gold nanorod on fiber surface plasmon resonance (SPR) sensor. It proposes modeling the sensing effects of fiber SPR sensor decorated with metal nanoparticles. By using simulation and experiment, the sensitivity enhancement effect of the gold nanorod was studied and demonstrated. Design/methodology/approach: The paper opted for an exploratory study using simulation approach of finite-difference time-domain. Specifically, the effect of ratios and aspect ratios of gold nanorod on sensing performance are investigated theoretically. Based on the mathematical models, the validation experiments by using the gold nanorod with the aspect ratios of 5.1 were done to verify the sensitivity enhancement effect of the gold nanorod. Findings: In conclusion, it is evident that with the increases of the aspect ratios, the sensing sensitivity of the refractive index increases first, then gradually stabilizes or decreases. After parameter optimization, the ratios and aspect ratios of gold nanorod are chosen to be 8 nm and 12.5, respectively, which makes the optimal refractive index sensitivity of 4465.53 nm/RIU be realized. In addition, the validation experiments by using the gold nanorod with the aspect ratios of 5.1 verify the sensitivity enhancement effect of the gold nanorods. Originality/value: This paper proposes and demonstrates a new method for the sensitivity enhancement of fiber SPR sensor. After parameter optimization, the maximum sensitivity of 4465.53 nm/RIU was achieved by using 8 nm gold nanorods with the aspect ratios of 12.5. To verify the sensitivity enhancement of the gold nanorods, the authors also did the validation experiments. The testing results indicated that after the decoration of the gold nanorods, the sensitivity of the sensing probe increases from 2190.57 nm/RIU to 2693.24 nm/RIU, which demonstrates the sensitivity enhancement effect of the gold nanorods.